1997
DOI: 10.1021/jm9700068
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of TBC11251, a Potent, Long Acting, Orally Active Endothelin Receptor-A Selective Antagonist

Abstract: Previously we reported the discovery of amidothiophenesulfonamides as endothelin receptor-A antagonists with high potency and selectivity. Replacement of an amide group in this class of compounds with an acetyl group maintained the in vitro binding affinity and in vivo activity while providing a compound with oral bioavailability and longer duration of action. The optimal compound discovered during these studies, 15q (TBC11251), binds competitively to human ETA receptors with a Ki of 0.43 +/- 0.03 nM and an IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(56 citation statements)
references
References 5 publications
3
53
0
Order By: Relevance
“…Bosentan (Ro 47-0203; 4-tert-butyl-N-[6-(2-hydroxy-ethoxy)-5-(2-methoxy-phenoxy)-2,29-bipyrimidin-4-yl]-benzenesulfonamide) (Clozel et al, 1994) was synthesized by Medicinal Chemistry, AstraZeneca (Mölndal, Sweden). Sitaxentan (TBC11251; N-(4-chloro-3-methyl-1,2-oxazol-5-yl)-2-[2-(6-methyl-2H-1,3-benzodioxol-5-yl)acetyl]thiophene-3-sulfonamide) (Wu et al, 1997) and ambrisentan (BSF208075; LU208075; (2S)-2-[(4,6-dimethylpyrimidin-2-yl)oxy]-3-methoxy-3,3-diphenylpropanoic acid) (Riechers et al, 1996) were obtained from Chemtronica AB (Stockholm, Sweden). THLE cell lines (1A2, 2C9, 2C19, 2D6, 3A4, and Null) were obtained from Nestec (Lausanne, Switzerland).…”
Section: Methodsmentioning
confidence: 99%
“…Bosentan (Ro 47-0203; 4-tert-butyl-N-[6-(2-hydroxy-ethoxy)-5-(2-methoxy-phenoxy)-2,29-bipyrimidin-4-yl]-benzenesulfonamide) (Clozel et al, 1994) was synthesized by Medicinal Chemistry, AstraZeneca (Mölndal, Sweden). Sitaxentan (TBC11251; N-(4-chloro-3-methyl-1,2-oxazol-5-yl)-2-[2-(6-methyl-2H-1,3-benzodioxol-5-yl)acetyl]thiophene-3-sulfonamide) (Wu et al, 1997) and ambrisentan (BSF208075; LU208075; (2S)-2-[(4,6-dimethylpyrimidin-2-yl)oxy]-3-methoxy-3,3-diphenylpropanoic acid) (Riechers et al, 1996) were obtained from Chemtronica AB (Stockholm, Sweden). THLE cell lines (1A2, 2C9, 2C19, 2D6, 3A4, and Null) were obtained from Nestec (Lausanne, Switzerland).…”
Section: Methodsmentioning
confidence: 99%
“…6 We previously found that short-term systemic administration of sitaxsentan caused a greater decrease in pulmonary versus systemic vascular tone in patients with moderate to severe HF, suggesting that ET plays a role in mediating pulmonary hypertension in such patients. 7 To directly test this hypothesis, sitaxsentan was infused into a segmental pulmonary artery, and the effect on pulmonary arterial tone was assessed by measuring the change in local blood flow velocity using a Doppler-tipped wire in patients with left ventricular (LV) systolic failure and control subjects with normal LV function.…”
mentioning
confidence: 90%
“…TBC-3214 (25 mg/kg body wt; Texas Biotechnology) was dissolved in drinking water, administered 3-5 days before surgery, and continued for the duration of the specific experimental group (i.e., 1 and 5 days or 8 wk postfistula). This dose of TBC-3214 was selected based on the manufacturer's (Texas Biotechnology) specified oral bioavailability concentrations documented in previous in vitro studies (42,53,54). Use of this class of ETA receptor antagonist in heart failure patients was capable of improving pulmonary hemodynamics but did not affect systemic vascular resistance (for review, see Ref.…”
Section: Animal Welfarementioning
confidence: 99%